PENDAMPINGAN DIGITALISASI UMKM DI KOTA CIREBON: MENINGKATKAN DAYA SAING MELALUI TRANSFORMASI TEKNOLOGI - Dewi Wahyuni; Indra Surya Permana (Aspirasi Masyarakat, 2024)
This community service program aims to improve the digitalization capabilities of Micro, Small, and Medium Enterprises (MSMEs) in Cirebon City. Digitalization is an important key for MSMEs in increasing competitiveness, especially after the COVID-19 pandemic, which has accelerated the shift of businesses to digital platforms. This program focuses on training in the use of digital technology, from digital marketing to application-based financial management. Through a participatory approach, MSMEs are given direct training on the use of social media, e-commerce, and digital payment applications. The results of this program show a significant increase in MSME digital literacy, as reflected in increased customer interaction, sales growth, and operational efficiency. However, there are several challenges such as limited time for assistance and infrastructure that is not evenly distributed in several regions. Overall, this program makes an important contribution to encouraging the digital transformation of MSMEs in Cirebon City and has implications for the development of broader digitalization policies for MSMEs in Indonesia.